2009
DOI: 10.1007/s12275-008-0307-8
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular substrates of a heme-containing ascorbate oxidase in Pleurotus ostreatus

Abstract: A novel heme-containing ascorbate oxidase isolated from oyster mushroom, Pleurotus ostreatus, catalyzes oxidation of ascorbic acid (Kim et al., 1996). In this report, we describe the identification of intracellular substrates of the enzyme in the mushroom. Six compounds, which can serve as substrate of the heme-containing ascorbate oxidase, were identified as L-ascorbic acid, D-erythroascorbic acid, 5-O-(alpha-D-glucopyranosyl)-D-erythroascorbic acid, 5-O-(alpha-D-xylopyranosyl)-D-erythroascorbic acid, 5-methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
(18 reference statements)
1
12
0
Order By: Relevance
“…The concentration of hydrogen peroxide produced was quite similar to that of the reductones oxidized (Lee et al, 2009). It has been reported that ascorbate oxidase was detected only in the mycelial stage of development in P. ostreatus (Kim et al, 1996).…”
supporting
confidence: 67%
See 4 more Smart Citations
“…The concentration of hydrogen peroxide produced was quite similar to that of the reductones oxidized (Lee et al, 2009). It has been reported that ascorbate oxidase was detected only in the mycelial stage of development in P. ostreatus (Kim et al, 1996).…”
supporting
confidence: 67%
“…Ascorbic acid, erythroascorbic acid and an additional four reductones such as 5-O-(Į-glucopyranosyl)--erythroascorbic acid, 5-O-(Į--xylopyranosyl)--erythroascorbic acid, 5-methyl-5-O-(Į--glucopyranosyl)--erythroascorbic acid and 5-methyl-5-O-(Į--xylopyranosyl)--erythroascorbic acid have been identified in the fruit body of the oyster mushroom P. ostreatus and other basidiomycetes (Okamura, 1994;Lee et al, 2009). The enzymes involved in the ascorbate system were isolated from the vegetative mycelia of P. ostreatus and characterized.…”
mentioning
confidence: 99%
See 3 more Smart Citations